(untitled) (Dermatology Reports, 2022)
Late-onset focal dermal elastosis is a rare cutaneous condition classified as an increased dermal elastic tissue disorder. It is distinguished clinically by multiple papules with a preference for the neck and other flexures, as well as histologically by focally increased elastic fibers in the reticular dermis. Several elastic tissue disorders in the skin have a similar clinical presentation. The distinction between late-onset focal dermal elastosis and other pseudoxanthoma elasticum mimickers is critical because they are not associated with systemic lesions. We present a case of late-onset focal dermal elastosis and conduct a literature review on this unusual condition.